Influence of the injected beam parameters on the capture efficiency of an electron cyclotron resonance based charge breeder - A. Galatà; D. Mascali; G. Torrisi; L. Neri; L. Celona; J. Angot (Physical Review Accelerators and Beams, 2017)
Electron cyclotron resonance ion sources based charge breeders (ECR-CB) are fundamental devices for Isotope Separation On Line (ISOL) facilities aiming at postaccelerating radioactive ion beams (RIBs). Presently, low intensity RIBs do not allow a conventional tuning of the ECR-CB: as a consequence, it has to be set with a stable 1+ pilot beam first, switching then to the radioactive one without changing any parameter; this procedure is usually called “blind tuning.” Besides having different masses, pilot and radioactive beams can also differ in terms of the rms transverse emittance ε_{rms} and/or longitudinal energy spread ΔE, so the choice of a given pilot beam can determine the overall performances of the final breeding stage. This paper shows a numerical study of how the capture efficiency of the PHOENIX charge breeder is affected by the aforementioned beam paramaters: the analysis reveals the two-step nature of the process, highlighting the role of the injection optics and the plasma capture capability in the overall performances of this device. The simulations predict highest efficiency for ε_{rms}<5π  mm mrad and ΔE<5  eV in a optimum energy range between 2 and 6 eV, thus giving important information on the possibility of blindly tuning an ECR-CB. No isotopical effects were observed, while it clearly came out the necessity to improve the 1+ beam characteristics with a rf beam cooler prior to the injection into an ECR-CB.